2014
DOI: 10.3892/ijo.2014.2614
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced signaling pathways that promote cancer cell survival (Review)

Abstract: Radiation therapy is a staple cancer treatment approach that has significantly improved local disease control and the overall survival of cancer patients. However, its efficacy is still limited by the development of radiation resistance and the presence of residual disease after therapy that leads to cancer recurrence. Radiation impedes cancer cell growth by inducing cytotoxicity, mainly caused by DNA damage. However, radiation can also simultaneously induce multiple pro-survival signaling pathways, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(134 citation statements)
references
References 95 publications
6
126
0
2
Order By: Relevance
“…Combined siRNA knockdown of both EPH-A2 and EPH-B2 genes, herein, shown and known [18] to be overexpressed in ERMS tumours, replicated many of the phenotypic effects observed in ERMS cells after drug exposure, confirming that GLPG1790 activity is mediated by the efficient impairment of EPH activity [21]. Finally, our data underline the role of GLPG1790 exposure in potentiating the effects of radiotherapy, which usually works by inducing DSBs as well as by inhibiting the non-homologous end joining (NHEJ) and the homologous recombination (HR) DNA repair pathways in exposed tumour cells [47]. Indeed, GLPG1790 enhanced radiosensitivity of ERMS cell lines, as demonstrated by the clonogenic survival reduction of more Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Combined siRNA knockdown of both EPH-A2 and EPH-B2 genes, herein, shown and known [18] to be overexpressed in ERMS tumours, replicated many of the phenotypic effects observed in ERMS cells after drug exposure, confirming that GLPG1790 activity is mediated by the efficient impairment of EPH activity [21]. Finally, our data underline the role of GLPG1790 exposure in potentiating the effects of radiotherapy, which usually works by inducing DSBs as well as by inhibiting the non-homologous end joining (NHEJ) and the homologous recombination (HR) DNA repair pathways in exposed tumour cells [47]. Indeed, GLPG1790 enhanced radiosensitivity of ERMS cell lines, as demonstrated by the clonogenic survival reduction of more Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Even if the relationship between EPH/Ephrin signalling, DSB repair machinery and response to RT is still largely unknown; a correlation between EPH overexpression and the acquisition of a radioresistant phenotype has been reported in other solid tumours [34,35,49,50]. Here, we showed that GLPG1790 abrogates the RT-induced ATM and DNA-PKcs phosphorylation, whose activation is linked to the HR and NHEJ pathways, respectively [47]. Augmentation of radiation response by GLPG1790 treatment was also confirmed by our preliminary in vivo experiments, in which the combination therapy with GLPG1790 and fractionated radiation was significantly more effective than the drug or the RT alone in reducing tumour masses.…”
Section: Discussionmentioning
confidence: 56%
“…This argument is also applicable to those studies, in which inhibition of Akt and increased apoptosis were observed after targeting of upstream regulators of Akt, such as EGFR [131]. Given that radiosensitization can be achieved by enhancing different modes of cell death , such as mitotic catastrophe, autophagy, senescence [132][133][134] and apoptosis, the specific role of apoptosis as a mechanism of radiosensitization in solid tumors in general, and especially following Akt targeting, is questionable and requires further investigation.…”
Section: Importance Of Akt In Radiotherapy Resistancementioning
confidence: 85%
“…Currently, there are several drugs such as lithium chloride, valproic acid, olanzapine, and cimetidine, among others, which are used to treat other diseases but have shown an inhibitory effect on GSK3β [134] . It has been reported that glioblastomas have defects in apoptotic pathways including Bcl-2 [140,141] , which is also a downstream target of the PI3K/Akt pathway [142] . Cancer cells are protected from apoptosis by the up-regulation of various anti-apoptotic molecules such as Bcl-2, which has been reported to be overexpressed in glioblastoma [143,144] .…”
Section: Pi3k/akt/mtormentioning
confidence: 99%